The Principle of Constitutional Independence in Light of the Principle of Non-Intervention in Internal Affairs - توفيق, فيصل صادق; عبدالله, خاموش عمر (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
This research addresses the issue of constitutional independence of the state and its relationship with the concept of sovereignty and the principle of non-intervention in internal affairs according to international law. The study emphasizes that the constitution is an expression of the state’s sovereignty and independence in choosing a system of governance that meets the aspirations of its people without external interference, while adhering to modern international principles and requirements. As international law has evolved, sovereignty has become a relative concept, transitioning from absolute sovereignty to one conditioned by responsibilities towards citizens, security, and international peace. The principle of non-intervention is no longer the inviolable principle it once was; instead, it has become more flexible, influenced by international changes and developments such as the protection of human rights, the promotion of peace, and the defense of legitimate governments. These factors have sometimes justified intervention in the internal affairs of other states to prevent the escalation of international crises. The research employs an analytical approach and is divided into two main sections: the first addresses the nature of the principle of constitutional independence, and the second discusses the principle of non-intervention in internal affairs and its direct connection to constitutional independence. The study concludes with several findings that affirm the right of states to exercise their internal sovereignty while considering international responsibilities.